A Dynamic Problem of a Crack in a Plate Strip - Kuhn, G.; Matczyński, M. (Engineering Transactions, 1974)
In this paper discussed is the quasi-static problem of displacement and stress distribution in an infinite elastic strip containing a semi-infinite crack located in its middle plane. The crack is assumed to propagate at a constant velocity along the straight line lying in the middle plane of the strip. Using the integral Fourier transforms, the problem is reduced to a corresponding Wiener-Hopf equation. The value of the stress intensity factor at the tip of the crack is accurately determined. Numerical evaluation of the inverse Fourier transforms yields the distribution of stress and displacement components at an arbitrary point of the strip. The results are illustrated by graphs.